2013
DOI: 10.1017/s1742170512000385
|View full text |Cite
|
Sign up to set email alerts
|

Targeting perennial vegetation in agricultural landscapes for enhancing ecosystem services

Abstract: Over the past century, agricultural landscapes worldwide have increasingly been managed for the primary purpose of producing food, while other diverse ecosystem services potentially available from these landscapes have often been undervalued and diminished. The incorporation of relatively small amounts of perennial vegetation in strategic locations within agricultural landscapes dominated by annual crops-or perennialization-creates an opportunity for enhancing the provision of a wide range of goods and service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
184
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(190 citation statements)
references
References 305 publications
(380 reference statements)
6
184
0
Order By: Relevance
“…Schulte et al 18 suggested that the strategic integration of perennial vegetation into agricultural landscapes dominated by annual crops could help reconcile agricultural productivity with environmental quality. Increasing crop and non-crop diversity in agroecosystems with perennial species may be especially important because perennial plants perform many key ecological functions more effectively than annuals, including (1) regulating the flow and storage of water, (2) reducing soil erosion, (3) storing and cycling nutrients and carbon, and (4) providing habitat for natural enemies of crop pests and for native plants and animals of conservation concern 18,19 . Many options exist for diversifying agroecosystems with perennial vegetation, including forage crops that are alternated with row crops in rotation sequences; riparian buffers of trees, shrubs and grasses that separate crop fields from streams; in-field strips of herbaceous species that filter runoff water; trees and shrubs on field margins that reduce wind movement; reconstructed wetlands that receive drainage water from crop fields; agroforestry plantations that supply a variety of economic products; and woody and herbaceous plants that are harvested as biofuel feedstocks 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Schulte et al 18 suggested that the strategic integration of perennial vegetation into agricultural landscapes dominated by annual crops could help reconcile agricultural productivity with environmental quality. Increasing crop and non-crop diversity in agroecosystems with perennial species may be especially important because perennial plants perform many key ecological functions more effectively than annuals, including (1) regulating the flow and storage of water, (2) reducing soil erosion, (3) storing and cycling nutrients and carbon, and (4) providing habitat for natural enemies of crop pests and for native plants and animals of conservation concern 18,19 . Many options exist for diversifying agroecosystems with perennial vegetation, including forage crops that are alternated with row crops in rotation sequences; riparian buffers of trees, shrubs and grasses that separate crop fields from streams; in-field strips of herbaceous species that filter runoff water; trees and shrubs on field margins that reduce wind movement; reconstructed wetlands that receive drainage water from crop fields; agroforestry plantations that supply a variety of economic products; and woody and herbaceous plants that are harvested as biofuel feedstocks 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Perennial crops contribute to a mixture of population communities with different "ecological ages", which was proposed by Odum [147] for nature conservation in landscape planning [153]. A strategic placement of perennial plants in agricultural landscapes, either on-field or adjacent, likely provides greater benefits than their spatial extent suggests [11,122].…”
Section: Potentials For Nature Conservationmentioning
confidence: 99%
“…Much of the dysfunction of industrial agriculture in the Corn Belt derives from the low levels of biological diversity now present across landscapes and within farming systems in the region (Broussard and Turner, 2009;Liebman et al, 2013;Asbjornsen et al, 2014). Of particular importance is the fact that shallow-rooted, short-season crops like corn and soybean have replaced native, perennial species whose deep roots and long growth period from early spring to late fall are much more effective in holding soil in place, promoting water infiltration into soil and transpiration into the atmosphere, fostering carbon sequestration and nutrient retention, and providing habitat for pollinators, biological control agents, and a host of other organisms .…”
mentioning
confidence: 99%
“…Although we have presented just two case studies of how diversification might be used to enhance agroecosystem performance and resilience in the U.S. Corn Belt, studies conducted in other regions also support diversification as a key principle underpinning the design of multifunctional agroecosystems that provide a wide range of goods and services while protecting environmental quality (Altieri, 1995;Kremen and Miles, 2012;Asbjornsen et al, 2014). Additional options for diversifying landscapes and cropping systems include the use of mixed species pastures for dairy and beef production (Sulc and Tracy, 2007); perennial grains for food and feed production (Cox et al, 2006); cover crops to fill otherwise unoccupied temporal niches (Snapp et al, 2005); dedicated perennial grasses and native mixed-species communities for biofuel feedstock production (Heaton et al, 2013); herbaceous and woody species for reconstructing wetlands (Zedler, 2003) and riparian corridors (Schultz et al, 2004); and trees for agroforestry plantations ( Jose et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation